Leak-proof environment-friendly green cosmetic sealing bottle and preparation method thereof
By mixing the polyethylene resin and ductoothyl polyvinyl branching, and antioxidants, and modified polyethylene dilately glycols, the polyethylene material has poor mechanical performance, non -antibacterial, and non -degradable. The problem realizes the environmentally friendly green cosmetics sealing bottle material with high strength, gas tightness and antibacterial properties.
Patent Information
- Application Number
- CN202411439388.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The polyethylene materials used in cosmetic packaging bottles have poor mechanical properties and are not antibacterial and degradable.
The 60-90 weight polyethylene resin, 10-40 ductoon ammonium-based polyethylene glycol branches PET and 0.2-0.6 weight-weight antioxidants are mixed materials. Compatible with polyethylene resin, and add a daily ammonium salt antibacterial group.
It improves the stretching intensity and fracture and elongation of materials, enhances gas tightness and anti -penetration performance, and significantly improves the antibacterial rate of E. coli and Staphylococcus aureus, and has good antibacterial properties and degradability.
Smart Images

Figure BDA0005085951720000021 
Figure BDA0005085951720000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic packaging bottles, in particular to a leakage-proof, environment-friendly, green cosmetic sealed bottle and a preparation method thereof. Background Art
[0002] Polyethylene is a common polymer plastic, widely used in cosmetic packaging bottles, food and medicine packaging and other fields. However, polyethylene materials are not biodegradable and cause great environmental pollution after being discarded, which is one of the causes of white pollution. By blending polyethylene with biodegradable materials such as polyethylene terephthalate and polylactic acid, a biodegradable composite material with better performance can be obtained.
[0003] Polyethylene terephthalate has high mechanical strength, low water vapor permeability and oxygen permeability, good air tightness, excellent barrier properties, and has important applications in packaging materials. Polyethylene terephthalate has poor compatibility with polyethylene, and usually requires the addition of a compatibilizer; the invention patent with announcement number CN104151670B discloses a high-density polyethylene and PET alloy tube and a preparation method thereof, using polyethylene, polyethylene terephthalate, a compatibilizer, a reinforcing agent, etc. as raw materials, and the obtained PE / PET alloy tube has higher strength, modulus, surface hardness and other properties. However, PE / PET materials do not have antibacterial properties, which is not conducive to their practical application in cosmetic packaging, food and drug packaging, etc. Summary of the invention
[0004] The technical problem solved by the present invention is to provide a leakage-proof, environmentally friendly, green cosmetic sealed bottle and a preparation method thereof, which solves the problem that the polyethylene material used for cosmetic packaging bottles has poor mechanical properties and lacks antibacterial and degradable properties.
[0005] The technical solution provided by the present invention includes: an anti-leakage environmentally friendly green material, including 60-90 parts by weight of polyethylene resin, 10-40 parts by weight of quaternized polyvinyl alcohol grafted PET, and 0.2-0.6 parts by weight of antioxidant;
[0006] The preparation method of quaternized polyvinyl alcohol grafted PET comprises: adding polyethylene terephthalate to tetrachloroethane, heating to 70-80°C, adding toluene-2,4-diisocyanate and butyltin dilaurate after stirring, reacting for 3-5 hours to obtain terminal isocyanate PET, then adding N,N-dimethylformamide solution of quaternized polyvinyl alcohol, continuing to react for 48-60 hours, cooling and pouring the solution into ethanol for precipitation, filtering, washing with ethanol and water, and drying to obtain quaternized polyvinyl alcohol grafted PET.
[0007] Furthermore, the masses of toluene-2,4-diisocyanate, butyltin dilaurate, and quaternized polyvinyl alcohol are 3.2-3.8%, 0.05-0.06%, and 14-22% of the mass of polyethylene terephthalate, respectively.
[0008] Furthermore, the preparation method of quaternized polyvinyl alcohol includes: adding polyvinyl alcohol to water, heating to 95°C, stirring and dissolving, cooling to 50-60°C, adding potassium hydroxide to adjust the solution pH to 10-11, and then adding 2,3-epoxypropyltrimethylammonium chloride, reacting for 2-4 hours, cooling, adding hydrochloric acid solution to adjust the pH to neutral, heating and volatilizing until a large amount of precipitate is precipitated, cooling and filtering, washing with ethanol, and drying to obtain quaternized polyvinyl alcohol. The reaction formula is:
[0009]
[0010] Further, the mass of 2,3-epoxypropyltrimethylammonium chloride is 42-50% of the mass of polyvinyl alcohol.
[0011] Furthermore, the preparation method of the leakage-proof environmentally friendly green material includes: adding polyethylene resin, quaternized polyvinyl alcohol grafted PET, and an antioxidant into a high-speed mixer, mixing at 60-70°C for 5-10 minutes, and then placing the materials in a twin-screw extruder for melt extrusion, the temperature of zones 1-7 is 180-270°C, and granulating to obtain the leakage-proof environmentally friendly green material.
[0012] Furthermore, a leak-proof, environmentally friendly, green cosmetic sealed bottle is made of leak-proof, environmentally friendly, green materials.
[0013] The technical effect of the present invention is as follows: the present invention utilizes the hydroxyl group of polyvinyl alcohol to react with the epoxy group of 2,3-epoxypropyltrimethylammonium chloride to obtain quaternized polyvinyl alcohol, and at the same time, the hydroxyl group and the epoxy group undergo a ring-opening reaction to generate a hydroxyl group. The present invention reacts the toluene-2,4-diisocyanate with the terminal hydroxyl group of polyethylene terephthalate to obtain terminal isocyanate PET, and the terminal isocyanate group thereof reacts with the hydroxyl group of quaternized polyvinyl alcohol to obtain quaternized polyvinyl alcohol grafted PET, and finally melt-blended with polyethylene resin to obtain a leakage-proof environmentally friendly green material.
[0014] After the PET of the present invention is modified by grafting with polyvinyl alcohol, the compatibility with polyethylene resin is better, the tensile strength and elongation at break of the obtained material are higher, and the water vapor permeability is lower, the air tightness is better, and it is beneficial to improve the anti-seepage and anti-leakage capabilities of the material. In addition, the polyvinyl alcohol grafted with PET contains a large amount of quaternary ammonium salt antibacterial groups, which significantly improves the antibacterial rate of the material to Escherichia coli and Staphylococcus aureus, and shows good antibacterial performance.
[0015] The anti-leakage environmentally friendly green material of the invention contains degradable polyvinyl alcohol and polyethylene terephthalate components, is green and environmentally friendly, has good antibacterial properties, and has good practical applications in cosmetic packaging bottles and the like. DETAILED DESCRIPTION
[0016] In order to understand the technical features and contents of the present invention in detail, the preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described in the embodiments, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described here.
[0017] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.
[0018] Polyethylene resin, Suzhou Jishao Engineering Plastics Co., Ltd.
[0019] Polyethylene terephthalate, Dongguan Hangyi Hot Melt Adhesive Co., Ltd.
[0020] Example 1
[0021] Step (1), add 5g of polyvinyl alcohol to 80mL of water, heat to 95°C, stir to dissolve and then cool to 50°C, add potassium hydroxide to adjust the pH of the solution to 11, then add 2.3g of 2,3-epoxypropyltrimethylammonium chloride, react for 4h, cool and add hydrochloric acid solution to adjust the pH to neutral, heat and volatilize until a large amount of precipitate is precipitated, cool and filter, wash with ethanol, and dry to obtain quaternized polyvinyl alcohol.
[0022] Step (2), add 50g of polyethylene terephthalate to 800mL of tetrachloroethane, heat to 80°C, add 1.7g of toluene-2,4-diisocyanate and 27mg of butyltin dilaurate after stirring, react for 3h to obtain terminal isocyanate PET, then add 140mL of N,N-dimethylformamide solution containing 9g of quaternized polyvinyl alcohol, continue to react for 60h, cool and pour the solution into ethanol for precipitation, filter, wash with ethanol and water, and dry to obtain quaternized polyvinyl alcohol grafted PET.
[0023] Step (3), adding 900g polyethylene resin, 100g quaternized polyvinyl alcohol grafted PET, and 6g antioxidant 1076 into a high-speed mixer, mixing at 60°C for 10min, and then placing the materials into a twin-screw extruder for melt extrusion, with the temperatures in zones 1-7 being 180°C, 210°C, 240°C, 240°C, 260°C, 270°C, and 270°C, and granulating to obtain a leakage-proof, environmentally friendly, green material.
[0024] Example 2
[0025] Step (1), add 5g of polyvinyl alcohol to 80mL of water, heat to 95°C, stir to dissolve and then cool to 50°C, add potassium hydroxide to adjust the pH of the solution to 10, then add 2.1g of 2,3-epoxypropyltrimethylammonium chloride, react for 3h, cool and add hydrochloric acid solution to adjust the pH to neutral, heat and volatilize until a large amount of precipitate is precipitated, cool and filter, wash with ethanol, and dry to obtain quaternized polyvinyl alcohol.
[0026] Step (2), add 50g of polyethylene terephthalate to 700mL of tetrachloroethane, heat to 70°C, add 1.6g of toluene-2,4-diisocyanate and 25mg of butyltin dilaurate after stirring, react for 5h to obtain terminal isocyanate PET, then add 120mL of N,N-dimethylformamide solution containing 7g of quaternized polyvinyl alcohol, continue to react for 48h, cool and pour the solution into ethanol for precipitation, filter, wash with ethanol and water, and dry to obtain quaternized polyvinyl alcohol grafted PET.
[0027] Step (3), adding 800g polyethylene resin, 200g quaternized polyvinyl alcohol grafted PET, and 6g antioxidant 1076 into a high-speed mixer, mixing at 70°C for 5min, and then placing the materials into a twin-screw extruder for melt extrusion, with the temperatures in zones 1-7 being 180°C, 210°C, 240°C, 240°C, 260°C, 270°C, and 270°C, and granulating to obtain a leakage-proof, environmentally friendly, green material.
[0028] Example 3
[0029] Step (1), add 5g of polyvinyl alcohol to 120mL of water, heat to 95°C, stir to dissolve and then cool to 55°C, add potassium hydroxide to adjust the pH of the solution to 10, then add 2.5g of 2,3-epoxypropyltrimethylammonium chloride, react for 4h, cool and add hydrochloric acid solution to adjust the pH to neutral, heat and volatilize until a large amount of precipitate is precipitated, cool and filter, wash with ethanol, and dry to obtain quaternized polyvinyl alcohol.
[0030] Step (2), add 50g of polyethylene terephthalate to 800mL of tetrachloroethane, heat to 80°C, add 1.7g of toluene-2,4-diisocyanate and 30mg of butyltin dilaurate after stirring, react for 5h to obtain terminal isocyanate PET, then add 160mL of N,N-dimethylformamide solution containing 11g of quaternized polyvinyl alcohol, continue to react for 48h, cool and pour the solution into ethanol for precipitation, filter, wash with ethanol and water, and dry to obtain quaternized polyvinyl alcohol grafted PET.
[0031] Step (3), adding 700g polyethylene resin, 300g quaternized polyvinyl alcohol grafted PET, and 4g antioxidant 1076 into a high-speed mixer, mixing at 60°C for 10min, and then placing the materials into a twin-screw extruder for melt extrusion, with the temperatures in zones 1-7 being 180°C, 210°C, 240°C, 240°C, 260°C, 270°C, and 270°C, and granulating to obtain a leakage-proof, environmentally friendly, green material.
[0032] Example 4
[0033] Step (1), add 5g of polyvinyl alcohol to 100mL of water, heat to 95°C, stir to dissolve and then cool to 60°C, add potassium hydroxide to adjust the pH of the solution to 11, then add 2.3g of 2,3-epoxypropyltrimethylammonium chloride, react for 2h, cool and add hydrochloric acid solution to adjust the pH to neutral, heat and volatilize until a large amount of precipitate is precipitated, cool and filter, wash with ethanol, and dry to obtain quaternized polyvinyl alcohol.
[0034] Step (2), add 50g of polyethylene terephthalate to 900mL of tetrachloroethane, heat to 75°C, add 1.9g of toluene-2,4-diisocyanate and 30mg of butyltin dilaurate after stirring, react for 4h to obtain terminal isocyanate PET, then add 160mL of N,N-dimethylformamide solution containing 11g of quaternized polyvinyl alcohol, continue to react for 60h, cool and pour the solution into ethanol for precipitation, filter, wash with ethanol and water, and dry to obtain quaternized polyvinyl alcohol grafted PET.
[0035] Step (3), adding 600g polyethylene resin, 400g quaternized polyvinyl alcohol grafted PET, and 2g antioxidant 1076 into a high-speed mixer, mixing at 65°C for 10min, and then placing the materials in a twin-screw extruder for melt extrusion, with the temperatures in zones 1-7 being 180°C, 210°C, 240°C, 240°C, 260°C, 270°C, and 270°C, and granulating to obtain a leakage-proof, environmentally friendly, green material.
[0036] Comparative Example 1
[0037] Step (3), adding 900g polyethylene resin and 6g antioxidant 1076 into a high-speed mixer, mixing at 60°C for 10min, and then placing the material into a twin-screw extruder for melt extrusion, with the temperatures in zones 1-7 being 180°C, 210°C, 240°C, 240°C, 260°C, 270°C, and 270°C, and granulating to obtain a leakage-proof, environmentally friendly, green material.
[0038] Comparative Example 2
[0039] Step (1), adding 900g polyethylene resin, 100g polyethylene terephthalate, and 6g antioxidant 1076 into a high-speed mixer, mixing at 60°C for 10min, then placing the materials into a twin-screw extruder for melt extrusion, the temperatures in zones 1-7 are 180°C, 210°C, 240°C, 240°C, 260°C, 270°C, and 270°C, granulation is performed to obtain a leakage-proof, environmentally friendly, green material.
[0040] Comparative Example 3
[0041] Step (1), add 50g of polyethylene terephthalate to 800mL of tetrachloroethane, heat to 80°C, add 1.7g of toluene-2,4-diisocyanate and 27mg of butyltin dilaurate after stirring, react for 3h to obtain terminal isocyanate PET, then add 140mL of N,N-dimethylformamide solution containing 9g of polyvinyl alcohol, continue to react for 60h, cool and pour the solution into ethanol for precipitation, filter, wash with ethanol and water, and dry to obtain polyvinyl alcohol grafted PET.
[0042] Step (2), adding 900g polyethylene resin, 100g polyvinyl alcohol grafted PET, and 6g antioxidant 1076 into a high-speed mixer, mixing at 60°C for 10min, and then placing the materials into a twin-screw extruder for melt extrusion, with the temperatures in zones 1-7 being 180°C, 210°C, 240°C, 240°C, 260°C, 270°C, and 270°C, and granulating to obtain a leakage-proof, environmentally friendly, green material.
[0043] The leak-proof environmentally friendly green material is injection molded by an injection molding machine at an injection temperature of 260°C. Standard test specimens are made. The tensile properties are tested according to GB / T 1040.1-2018 standard.
[0044] The antibacterial property was tested according to the method of QB / T 2591-2003, and the test bacteria were Escherichia coli and Staphylococcus aureus. The anti-leakage environmentally friendly green material of comparative example 1 was used as a blank control sample. The anti-leakage environmentally friendly green materials of Examples 1-4 and comparative examples 2-3 were used as antibacterial plastic samples.
[0045] Antibacterial rate R = (BC) / B × 100%.
[0046] B is the average number of recovered bacteria (cfu / piece) in the blank control sample. C is the average number of recovered bacteria (cfu / piece) in the antibacterial plastic sample.
[0047] The leak-proof, environmentally friendly green material is pressed into a film, and the water vapor permeability of the film is tested using a water vapor permeability tester. The relative humidity is 100%. Each film sample is tested 5 times and the average value is taken.
[0048] The specific test results are shown in Table 1.
[0049] Table 1: Performance Test
[0050]
[0051] As shown in Table 1, compared with Comparative Example 1, in Examples 1-3, polyethylene resin and quaternized polyvinyl alcohol grafted PET are used as the material matrix. After PET is grafted with polyvinyl alcohol, it has better compatibility with polyethylene resin, and the obtained material has higher tensile strength and elongation at break, while the water vapor permeability is lower and the air tightness is better, which is conducive to improving the material's anti-seepage and anti-leakage capabilities. In addition, the polyvinyl alcohol grafted with PET contains a large amount of quaternary ammonium salt antibacterial groups, which significantly improves the material's antibacterial rate against Escherichia coli and Staphylococcus aureus, showing good antibacterial properties.
[0052] The polyethylene terephthalate of Comparative Example 2 has not been grafted with polyvinyl alcohol, and has poor compatibility with polyethylene resin. The material has low tensile strength and elongation at break, and does not contain quaternary ammonium salt antibacterial groups, so the material has almost no antibacterial properties.
[0053] The polyvinyl alcohol-grafted PET of Comparative Example 3 does not contain quaternary ammonium salt antibacterial groups, and the material has almost no antibacterial properties.
[0054] The above describes some embodiments of the present invention, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A leak-proof, environmentally friendly, green material, characterized in that: The anti-leakage environmentally friendly green material comprises 60-90 parts by weight of polyethylene resin, 10-40 parts by weight of quaternized polyvinyl alcohol grafted PET, and 0.2-0.6 parts by weight of antioxidant; The preparation method of the quaternized polyvinyl alcohol grafted PET comprises: adding polyethylene terephthalate to tetrachloroethane, heating to 70-80°C, adding toluene-2,4-diisocyanate and butyltin dilaurate after stirring, reacting for 3-5 hours, then adding N,N-dimethylformamide solution of quaternized polyvinyl alcohol, continuing the reaction for 48-60 hours, cooling and pouring the solution into ethanol for precipitation, filtering, washing with ethanol and water, and drying to obtain the quaternized polyvinyl alcohol grafted PET.
2. The anti-leakage environmentally friendly green material according to claim 1, characterized in that: The masses of the toluene-2,4-diisocyanate, butyltin dilaurate and quaternized polyvinyl alcohol are 3.2-3.8%, 0.05-0.06% and 14-22% of the mass of polyethylene terephthalate respectively.
3. The anti-leakage environmentally friendly green material according to claim 1, characterized in that: The preparation method of the quaternary ammonium polyvinyl alcohol comprises: adding polyvinyl alcohol to water, heating to 95° C., stirring to dissolve and then cooling to 50-60° C., adding potassium hydroxide, and then adding 2,3-epoxypropyltrimethylammonium chloride, reacting for 2-4 hours, cooling and adding hydrochloric acid solution to adjust the pH to neutral, heating and volatilizing until a precipitate is precipitated, cooling and filtering, washing with ethanol, and drying to obtain the quaternary ammonium polyvinyl alcohol.
4. The anti-leakage environmentally friendly green material according to claim 3 is characterized in that: The potassium hydroxide is added to adjust the solution pH to 10-11.
5. The anti-leakage environmentally friendly green material according to claim 3 is characterized in that: The mass of the 2,3-epoxypropyltrimethylammonium chloride is 42-50% of the mass of the polyvinyl alcohol.
6. A method for preparing the leakage-proof environmentally friendly green material according to any one of claims 1 to 5, characterized in that: The preparation method comprises: adding polyethylene resin, quaternized polyvinyl alcohol grafted PET and antioxidant into a high-speed mixer for mixing, then placing the materials into a twin-screw extruder for melt extrusion and granulation to obtain a leak-proof environmentally friendly green material.
7. The method for preparing the leakage-proof environmentally friendly green material according to claim 6, characterized in that: The temperature during mixing in the high-speed mixer is 60-70° C. and the mixing time is 5-10 min.
8. The method for preparing the leakage-proof environmentally friendly green material according to claim 6, characterized in that: The temperature of zones 1-7 of the twin-screw extruder is 180-270°C.
9. A leak-proof, environmentally friendly, green cosmetic sealed bottle made from the leak-proof, environmentally friendly, green material according to any one of claims 1 to 5.
Citation Information
Patent Citations
A kind of high-density polyethylene and pet alloy pipe and preparation method thereof
CN104151670B
KR20240073731A
Cited By
High-barrier-property antibacterial food packaging film and preparation method thereof
CN120888152A